The environmental state as a model for the world? An analysis of policy repertoires in 37 countries. Issue 1 (2nd January 2016) - Sommerer, Thomas; Lim, Sijeong
Abstract : Scholars have proposed the analytical concept of the environmental state, a state where government actively addresses negative environmental externalities of economic activities. The mapping of environmental regulatory expansion in Western countries has been central in recent attempts to identify the environmental state empirically. Surprisingly little is known, however, when it comes to the environmental regulatory expansions in non-Western countries. Are there similar trends towards the emergence of environmental states in the non-West as well? From analysing data covering 25 policies in 37 countries, it appears that regulatory expansion has also occurred in the non-Western world, and the distinction between the West and the non-West has been reduced over time. There are non-Western countries among environmental pioneers, and there is some evidence for the trend of global convergence. Future research on environmental states should take into account emerging environmental states in the non-West.